Characteristics of electrically evoked somatodendritic dopamine release in substantia nigra and ventral tegmental area in vitro. - Rice, M; Cragg, S; Greenfield, SA (1997)
Somatodendritic dopamine (DA) release from neurons of the midbrain represents a nonclassical form of neuronal signaling. We assessed characteristics of DA release during electrical stimulation of the substantia nigra pars compacta (SNc) in guinea pig midbrain slices. With the use of parameters optimized for this region, we compared stimulus-induced increases in extracellular DA concentration ([DA]o) in medial and lateral SNc, ventral tegmental area (VTA), and dorsal striatum in vitro. DA release was monitored directly with carbon-fiber microelectrodes and fast-scan cyclic voltammetry. Detection of DA in SNc was confirmed by electrochemical, pharmacological, and anatomic criteria. Voltammograms of the released substance had the same peak potentials as those of DA obtained during in vitro calibration, but different from those of the indoleamine 5-hydroxytryptamine. Similar voltammograms were also obtained in the DA-rich striatum during local electrical stimulation. Contribution from the DA metabolite 3,4-dihydroxyphenylacetic acid to somatodendritic release was negligible, as indicated by the lack of effect of the monoamine oxidase inhibitor pargyline (20 microM) on the signal. Lastly, DA voltammograms could only be elicited in regions that were subsequently determined to be positive for tyrosine hydroxylase immunoreactivity (TH-ir). The frequency dependence of stimulated DA release in SNc was determined over a range of 1-50 Hz, with a constant duration of 10 s. Release was frequency dependent up to 10 Hz, with no further increase at higher frequencies. Stimulation at 10 Hz was used in all subsequent experiments. With this paradigm, DA release in SNc was tetrodotoxin insensitive, but strongly Ca2+ dependent. Stimulated [DA]o in the midbrain was also site specific. At the midcaudal level examined, DA efflux was significantly greater in VTA (1.04 +/- 0.05 microM, mean +/- SE) than in medial SNc (0.52 +/- 0.05 microM), which in turn was higher than in lateral SNc (0.35 +/- 0.03 microM). This pattern followed the apparent density of TH-ir, which was also VTA > medial SNc > lateral SNc. This report has introduced a new paradigm for the study of somatodendritic DA release. Voltammetric recording with electrodes of 2-4 microns tip diameter permitted highly localized, direct detection of endogenous DA. The Ca2+ dependence of stimulated release indicated that the process was physiologically relevant. Moreover, the findings that somatodendritic release was frequency dependent across a range characteristic of DA cell firing rates and that stimulated [DA]o varied markedly among DA cell body regions have important implications for how dendritically released DA may function in the physiology and pathophysiology of substantia nigra and VTA.